Business transformation in a distinctive institutional setting: A study of regional development banks in Indonesia - Audy Thuda; Mohammad Hamsal; Dezie Leonarda Warganegara; Pantri Heriyati (Administrative Sciences, 2024)
Limited research exists on business transformation strategy within the Indonesian banking sector, particularly regarding regional development banks, which play a crucial role in regional economic advancement. This study investigates the drivers of successful business transformation in Indonesian RDBs and their impact on organizational performance, examining the moderating role of regional government intervention. Employing structural equation modeling, the study analyzed data from 255 branch managers across 27 RDBs. Results reveal that talent development, transformational leadership, and digital adoption significantly drive successful business transformation, which in turn enhances organizational performance. Contrary to expectations, regional government intervention did not demonstrate a moderating effect. This study provides valuable insights for RDB managers and policymakers, emphasizing the imporace of talent development, leadership, and digital adoption as key pillars of successful transformation and highlighting the need for a nuanced understanding of institutional influences within this sector
Keywords: 350; business transformation strategy; digital adoption; government intervention; transformational leadership; talent development